The Impact of Local Wisdom on the Coastal Settlement Spatial Configuration in the City of Parepare - Hasniar Baharuddin; Idarwani Asmal; Edward Syarif (EPI International Journal of Engineering, 2021)
Soreang Settlement is located on the waterfront of Parepare City in South Sulawesi, Indonesia. Initially, it was inhabited by the Soreang kingdom community and then developed due to by local culture. This research was to explain the influence of local culture on the spatial configuration of the Soreang settlement. The research method used is a synchronic reading analysis technique, which is supported by ArcGIS and the space syntax methods. The results of the research are: the first, the spatial configuration of Soreang settlements is influenced by three local cultures, namely sipakatau cultural meaning is sense mutual respect, sipakalebbi cultural meaning is sense of equity and simasemaseang cultural meaning is sense of family. The second, the simasemaseang culture, infact to a clustered settlement pattern formed. Sipakalebbi culture infact to settles into a linear and spreading pattern formed, whereas Sipakatau culture infact to a settles into an elongated and centered pattern formed. Third, Simasemaseang culture forms the most integrated spatial configuration. This research might well be utilized to generate a design for waterfront settlement based on local wisdom.